Exploring the Effect of Digital Storytelling on Employee Engagement: An Experiment Research - Bangun, Yuni Ros; Ginting, Henddy; Artini, Ratu Marlina (Jurnal Manajemen Teknologi, 2020)
Abstract. Employee engagement has been recognized as one of the strategies in delivering productivity and profitability growth in organizations. Working on to find the appropriate method to improve employee engagement, this study examines the effectiveness of digital storytelling as intervention method. This research is an experimental research where participants (n = 153) are assessed two times (pre-test and post-test) using two types of employee engagement assessment tools: questionnaire and text analysis. Experimental group accepts two times intervention of digital storytelling before post-test is given. A customized 12 dimensions of employee engagement is used in this experiment to construct the assessment tools. Paired t-test and independent t-test show significant improvement in the text analysis scores of employee engagement among participants with digital storytelling intervention, but not in the participant without the intervention. Further analyzes highlighted specific improvement in four dimensions (i.e., social support, work engagement, extra-role performance, and organization identity) from the 12 dimensions of employee engagement. Unfortunately, employee engagement assessment using questionnaire is insignificantly influenced by digital storytelling. This insignificant finding might be due to the ceiling effect of the questionnaire scores, but further investigation is needed to explained this results. This research demonstrate that digital storytelling is an effective method to improve employee engagement, and it is also efficient in time and cost.Keywords: Employee engagement, customized employee engagement, digital storytelling, text analysis, experimental research.Abstrak. Keterikatan karyawan dianggap sebagai salah satu strategi yang mendorong peningkatan produktivitas dan profitabilitas. Oleh karenanya, tingkat keterikatan karyawan menjadi penting. Dalam upaya menemukan metode yang tepat untuk meningkatkan keterikatan karyawan dalam perusahaan, penelitian ini menguji bagaimana efektivitas cerita digital apabila digunakan sebagai metode intervensi. Penelitian ini merupakan penelitian eksperimen, dimana peserta eksperimen (n=153) mengikuti dua kali penilaian keterikatan karyawan (pra-uji dan purna-uji) dengan menggunakan dua alat: kuesioner dan analisa teks. Kelompok eksperimen menerima dua kali intervensi cerita digital sedangkan kelompok control tidak mendapatkan intervensi. Pengukuran keterikatan karyawan pada penilitian ini menggunakan 12 dimensi pengukuran yang disesuaikan dengan tempat diadakannya eksperimen. Hasil uji paired t-test dan independent t-test menunjukkan peningkatan keterikatan karyawan pada kelompok eksperimen saat penilaian menggunakan analisa teks dan tidak pada kelompok kontrol. Hasil analisa selanjutnya menunjukkan bahwa peningkatan terjadi pada 4 dimensi pengukuran (dukungan social, keterikatan kerja, kinerja peran tambahan, dan identitas organisasi). Hanya saja peningkatan tersebut tidak terjadi pada kelompok eksperimen saat penilaian menggunakan kuesioner. Hal tersebut bisa dimungkinkan akibat dari ceiling-effect dari kuesioner. Walaupun demikian, penelitian lebih lanjut perlu dilakukan untuk menjelaskan hasil tersebut. Hasil penelitian ini menunjukkan bahwa cerita digital merupakan metode yang efektif untuk meningkatkan keterikatan karyawan dan efisien pada sisi waktu dan biaya.Kata kunci: Keterikatan karyawan, keterikatan karyawan yang disesuaikan, digital storytelling, analisa teks, penelitian experimental.